International Centers of Overseas Universities in the Global South: Lessons from India - Kumar, Nirved; Misra, Debananda (International Higher Education, 2024)
<h3 id="countries-of-the-global-south-have-been-exporting-students-to-universities-abroad-increasingly-there-is-more-internationalization-of-overseas-universities-into-the-global-south-countries-that-include-activities-such-as-research-public-engagement-and-working-with-governments-taking-indias-case-we-explore-an-emerging-mode-of-internationalization-in-the-global-south-by-setting-up-international-centers-in-host-countries-we-discuss-the-reasons-for-this-and-what-makes-such-centers-work" data-pm-slice="1 1 []">Countries of the Global South have been “exporting” students to universities abroad. Increasingly, there is more internationalization of overseas universities into the Global South countries that include activities such as research, public engagement, and working with governments. Taking India’s case, we explore an emerging mode of internationalization in the Global South by setting up “international centers” in host countries. We discuss the reasons for this and what makes such centers work.